STUDY OF THE INFLUENCE OF FACTORS ON THE MORPHOLOGICAL STRUCTURE OF CRYSTALS DURING ISOTHERMAL CRYSTALLIZATION - Яцюк, Илья (SWorldJournal, 2021)
Isothermal crystallization of ammonium sulfate is considered. The basic theoretical principles of the mass crystallization process are given, the factors influencing the morphological structure of ammonium sulfate crystals (temperature, level of solution